THE EFFECTS OF REMUNERATION ON THE EMPLOYEES’ PERFORMANCES AT THE PRESIDENTIAL PALACE IN JAKARTA - Pamuji, Kukuh; Susanto, Moh. Rusnoto; Putrianti, Flora Grace; Sudirman , Anselmus (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the effects of remuneration, self-efficacy, self-adversity and self monitoring on the employees’ performances. The research was conducted at the Presidential Palace in Jakarta using survey methods applied in structural equation models and hypothesis testing in which 117 samples were randomly selected. The results showed that (1) there is a positive direct influence on the performances of employees’ remuneration; (2) there is a positive direct effect of self-efficacy on the performances of employees; (3) there is a positive direct effect of adversity on the performances of employees; (4) there is a positive direct influence of self monitoring on the performancse of employees; and there is a jointly positive direct influence between the remuneration, self-efficacy, adversity, and self-monitoring of employees’ performances. Thus, the remuneration, self efficacy, adversity, and self-monitoring are important factors that determine the performances of the employees.